TRANSFORMASI STRUKTUR KETENAGAKERJAAN DAN PERTUMBUHAN EKONOMI SUMATERA SELATAN - Yunisvita Yunisvita (Department of Development Economics, Universitas Sriwijaya, 2011)
The result of Assessment on â€œChanges of Economic and Employment Structure as well as Quality of Human Resource in South Sumateraâ€ showed that in 2005-2010 periods economic (GNP) structure in Indonesia has been changed from S-I-A (Services-Industry- Agriculture) pattern to I-S-A pattern. Meanwhile, during the same period employment structure was remain stable, namely A-S-I pattern. The unbalanced changes between economic and employment structures were predicted to be the factors causing laborÂ productivity and society welfare in agricultural sector were declining. There was a quality improvement in human resource. However, the problem is government capability to create employment was not sufficient to provide job opportunity for improved human resource. Keywords: Changes, Structure, Economic, Employment, and Human Resource. .